2014
DOI: 10.1007/s10067-014-2768-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis is linked to worse outcomes and unfavourable treatment responses in patients with axial spondyloarthritis

Abstract: The diagnosis of spondyloarthritis (SpA) has a lengthy delay; we investigated the outcomes and factors associated with the delayed diagnosis of SpA. This was a cross-sectional study on patients with SpA who visited a rheumatology clinic at a single tertiary centre. The data were collected from face-to-face interviews, physician assessments of disease status and reviews of medical records. In total, 105 patients with SpA were consecutively enrolled. Of the included patients, 94 had axial SpA and 11 had peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 32 publications
5
118
0
4
Order By: Relevance
“…Although 9 papers mention the concepts of social events 21,47 , social support 21,42 , social system 21 , social situation 27,30 , effect and consequences 11,21 , social status 15,21,23,28 , social domain and function 31 , and quality of life 21,31 , they are not in relation to social/sex-related causes explaining sex differences in delay in diagnosis. Only Aggarwal in 2009 adequately discussed the complex range of sex factors involved in the diagnostic process of SpA according to sex 8 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although 9 papers mention the concepts of social events 21,47 , social support 21,42 , social system 21 , social situation 27,30 , effect and consequences 11,21 , social status 15,21,23,28 , social domain and function 31 , and quality of life 21,31 , they are not in relation to social/sex-related causes explaining sex differences in delay in diagnosis. Only Aggarwal in 2009 adequately discussed the complex range of sex factors involved in the diagnostic process of SpA according to sex 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease activity was the main variable associated to disability in patients with AS [2]. It has also been observed that disease activity contributes longitudinally to spinal radiographic progression in AS, being this effect more noticeable in early stages of the disease 3 .One study demonstrated that patients with a delayed diagnosis of axSpA of over 8 years have a higher disease activity, as well as more radiographic progression and worse functional disability [4]. Alternatively early treatment before the presence of irreversible structural damage might also reduce radiographic progression, as was reported recently in a prospective AS cohort [5].…”
mentioning
confidence: 99%